Occurrence of Transfusion Transmitted Infections Among Transfusion Dependent Thalassemia Patients in A Tertiary Care Hospital in India - Lyngdoh, Banduriap; Bagdi, Sunita; Ghosh, Sulekha; Ghosh, Tapan K (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: Blood transfusion is an important treatment modality in the modern health care system; however, transfusion transmitted infections(TTI) could be fatal or life-threatening in some cases. Objective: To determine the occurrence of transfusion transmitted infections among transfusion dependent thalassemia patients and to study the socio-demographic characteristics of the recipients. Methods: This hospital-based descriptive longitudinal studywas conducted between February 2019 and June 2020, on 102 transfusion-dependentthalassaemic patients receiving blood transfusion at Bankura Sammilani Medical College & Hospital, Bankura,West Bengal, India. They were tested for HIV, HBV, HCV, syphilis and malaria by ELISA (Enzyme Linked Immunosorbent Assay) Lisa Scan EM, Merilisa HBsAg, Merilisa HCV, RPR kit and Maleriscan malaria Pf/Pv. Results: Out of 102 patients, 5.90% were positive for TTI. The highest occurrence was found to be of HCV 3.90%. HBV and HIV showed similar occurrence of 0.98% and none came out positive for syphilis or malaria. The highest occurrence of TTI was found among females 66.7%. The average age of the participants was 7.97±3.27years. The average number of blood transfusion received per year was 11.95±2.71units. Majority of the participants belong to low socio- economic group family 62(60.8%). In respect to ethnicity 14.7%were tribal, while 85.3%were non-tribal population. Conclusion: The cause of high prevalence of HCV may be due to donors being asymptomatic in early stages and failure of detection due to window period of infection. More sensitive screening tests should be done for HIV, HBV, and HCV. All donors must be screened by NAT if not possible the patients must be screened for TTI regularly.Thalassemia patients being the most affected, premarital screening for thalassemia should be done.Every patient should be vaccinated with hepatitis B vaccine. International Journal of Human and Health Sciences Vol. 07 No. 02 Apr’23 Page: 171-175